VACCINE PREVENTION AND MICRONUTRIENTS - S.M. Kharit (Union of pediatricians of Russia, 2007)
It is well known that the vitamin deficiency may cause psychic and somatic disorders, as well as decrease functional activity of the immune system. Furthermore, the microelement deficiency may contribute to the growth of the pathological states among infants. this lecture summarizes the information from the literature, which allows assuming the positive effects of the vitamin and mineral complexes within the post vaccinal period among children due to activation of the immune reactions, prevention of the aggravated run of the vaccinal period (prevention of inter? current disease deposit and exacerbation of the background states, such as: perinatal nervous breakdowns, congenital infections and etc.), and probably, activation of the specific immune response.Key words: vaccine prevention, children, polyvitamins, immunity, prevention.